2013
DOI: 10.1186/gb-2013-14-7-r77
|View full text |Cite
|
Sign up to set email alerts
|

The genome and transcriptome of the enteric parasite Entamoeba invadens, a model for encystation

Abstract: BackgroundSeveral eukaryotic parasites form cysts that transmit infection. The process is found in diverse organisms such as Toxoplasma, Giardia, and nematodes. In Entamoeba histolytica this process cannot be induced in vitro, making it difficult to study. In Entamoeba invadens, stage conversion can be induced, but its utility as a model system to study developmental biology has been limited by a lack of genomic resources. We carried out genome and transcriptome sequencing of E. invadens to identify molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
159
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(176 citation statements)
references
References 104 publications
(143 reference statements)
16
159
0
1
Order By: Relevance
“…Thus the reptilian parasite, Entamoeba invadens , for which highly efficient in vitro encystation and excystation protocols exist, has been utilized as a model system to study Entamoeba development (Vazquezdelara-Cisneros and Arroyo-Begovich, 1984; Eichinger, 1997). Using this system, it has been shown that a number of processes including lipid signaling and meiosis are developmentally regulated (Ehrenkaufer et al, 2013). Additionally, as encystation progresses, the levels of metabolites involved in glycolysis decrease drastically (De Cadiz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the reptilian parasite, Entamoeba invadens , for which highly efficient in vitro encystation and excystation protocols exist, has been utilized as a model system to study Entamoeba development (Vazquezdelara-Cisneros and Arroyo-Begovich, 1984; Eichinger, 1997). Using this system, it has been shown that a number of processes including lipid signaling and meiosis are developmentally regulated (Ehrenkaufer et al, 2013). Additionally, as encystation progresses, the levels of metabolites involved in glycolysis decrease drastically (De Cadiz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order to define the transcriptional network associated with stage conversion, we recently performed RNA sequencing of E. invadens during the entire developmental cycle (both encystation and excystation) (Ehrenkaufer et al, 2013). The RNA-Seq methodology was used to improve the accuracy of genome annotation and identify untranslated regions as was demonstrated in E. histolytica (Hon et al, 2013), Tetrahymena (Xiong et al, 2012) and Plasmodium (Otto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the stability of silencing during the multitude of developmental changes is paramount in the use of this tool in different life cycle stages of the parasite. Recent transcriptome-sequencing (RNA-Seq) data from E. invadens has uncovered the fact that the sRNA repertoire does not change during the different developmental stages of the parasite (15). Therefore, we unfortunately did not find genes that could function as stage-specific triggers.…”
Section: Discussionmentioning
confidence: 42%
“…As the parasite undergoes a developmental shift from vegetative growth to a quiescent stage (trophozoites to cysts), approximately half of the E. invadens genome is differentially expressed at some point during the stage transition (15). Thus, it is imperative to determine if silencing is stable during this massive change in cell physiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation